A Good $λ$ Estimate for Multilinear Commutator of Singular Integral on Spaces of Homogeneous Type - Qian, Zhang; Lanzhe, Liu (Armenian Journal of Mathematics, 2011)
In this paper, a good $λ$ estimate for the multilinear commutator associated to the singular integral operator on the spaces of homogeneous type is obtained. Under this result, we get the$(L^p(X),L^q(X))$-boundedness of the multilinear commutator.